Rhizogenesis of regenerated shoot in Bangladeshi Sunflower (Helianthus annuus L.) varieties - Shormee, Sadia Zaman (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2016